Bentuk Kesalahan Pemakaian Bahasa Indonesia pada Media Luar Ruang di Wilayah Solo Raya - Lestari, Yunita Nur; Saddono, Kundharu (Efektor, 2024)
Language is an important part of communication. If there is good communication, then the role can work well. When one uses language in writing, it is important to follow the standards of the General Use of Indonesian Spelling (PUEBI) and the Big Indonesian Dictionary (KBBI). This is because the correct use of words is related to these rules. However, there are still many errors in language that occur in practice. This research uses a descriptive qualitative method. Observation, recording and documentation are the methods used by the researcher to collect data. The results of the analysis and research show that people in the Greater Solo area often make mistakes. Improper spelling and affixes are part of this kind of error